Health workers as surveillance officers role and cadres deal with pregnant women during the COVID-19 pandemic in Semarang, Indonesia - Arif Kurniadi; Dyah Ernawati; Kismi Mubarokah (Malahayati International Journal of Nursing and Health Science, 2021)
Background: Pregnancy is a difficult period and requires special attention and treatment because it can threaten the lifestyle of the mother and baby.Purpose: This study aims to determine the form of assistance for pregnant women with excessive threats that has been achieved to reduce maternal mortality (MMR) and infant mortality (IMR) in the city of Semarang.Method: This study uses a qualitative descriptive technique. The research sample is medical personnel who manipulate Maternal and Child Health (MCH) software, especially programmers for health institutional networks, health surveillance officers, and cadres in Central Semarang Regency.Results: Efforts to reduce the MMR/IMR achieved through the city health office is through the establishment of Maternal and Child Health Workers. Services in the building use the Public health center Information System Software. Maternal and Child Health Workers have a main mission to support and travel for pregnant and postpartum women, in addition to tracking and traveling at certain stages in pregnancy and postpartum through midwifery fitness offer, because the Maternal and Child Health surveillance officers recruited have a background in midwifery. The printing step for maternal and child health workers begins with making cadres documents in front of pregnant women.Conclusion: there is training for cadres and health surveillance officers on strong verbal exchanges, related to bidding with goals/clients (pregnant women and households).